2010
DOI: 10.5251/abjna.2010.1.3.350.354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of varietal feeding of eight Mulberry varieties on Bombyx mori L.

Abstract: The eight improved mulberry varieties i.e. S 146 , K 2 , S 1635 , AR 14 , TR 10 , BR 2 , S 1 & AR 12 were introduced in mulberry garden of Department of Applied Animal Sciences and theses varieties were evaluated for nutritional potential by feeding experiments. Weighted quantities of leaves of each variety were fed to mulberry silkworms and data were collected and evaluted. The larvae feeding on BR 2 leaves were observed the higher weight of mature larvae and showed improved economic traits i.e. cocoon weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…The present study also confirms the same where different host plants were evaluated for different silkworm strains. Gangawar (2010) found that among eight mulberry varieties screened for nutritional suitability, silkworm larvae fed on BR2 variety leaves showed increased larval weight and better economic traits in comparison to other varieties. In the present study, silk filament length of cocoons recovered from silkworms reared on different mulberry varieties falls within the range between 600 and 1500 m (FAO, 1999), and cocoons recovered from silkworms reared on Jorhat mulberry variety leaves produced the longest filament length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also confirms the same where different host plants were evaluated for different silkworm strains. Gangawar (2010) found that among eight mulberry varieties screened for nutritional suitability, silkworm larvae fed on BR2 variety leaves showed increased larval weight and better economic traits in comparison to other varieties. In the present study, silk filament length of cocoons recovered from silkworms reared on different mulberry varieties falls within the range between 600 and 1500 m (FAO, 1999), and cocoons recovered from silkworms reared on Jorhat mulberry variety leaves produced the longest filament length.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we would expect to find that different silkworm strains performed best on its most preferred host plants (Slansky and Scriber, 1985). The rearing performance of silkworm races are described in terms of larval weight and improved economic traits like cocoon weight, shell weight, and silk percentage (Gangawar, 2010; Seidavi, 2011). Cocoon weight and shell weight are the most important characteristics evaluated for productivity (Gaviria et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil analisis laboratorium terhadap kandungan nutrisi ketiga jenis murbei, SULI 01 menghasilkan kandungan protein lebih tinggi dibandingkan jenis lain (Tabel 2), dan sangat bagus sebagai pakan ulat karena pembentukan kelenjar sangat dipengaruhi oleh kandungan protein di daun murbei sebagai pakan ulat. Gangwar (2010) mengatakan bahwa tingkat gizi kultivar yang berbeda dari murbei memengaruhi pertumbuhan ulat, yang akhirnya memengaruhi sifat ekonominya seperti hasil kokon, bobot kulit kokon, dan persentase sutera dari ulat. Dalam hubungannya dengan kandungan zat-zat dalam daun murbei sebagai pakan, N (protein) merupakan bagian dari unit struktural dan sumber energi yang diperlukan dalam prosesproses sintesis di dalam tubuh ulat (Andikarya and Nunuh 2002) dan sangat erat hubungannya dengan pembentukan serat sutera (Kaomini 2002).…”
Section: Bobot Kokonunclassified
“…Previously, it is believed to have originated at the Himalayans foothills (Koidzumi, 1917). Earlier, Linneaus (1753) classified the genus Morus into five species on the basis of morphological characteristics: Morus alba, M. nigra, M. rubra, M. tartarica and M. indica L. The quality of the mulberry leaves has a direct impact on the normal growth and development of the larvae and also the quality of the cocoon (Legay, 1958; Adolkar et al, 2007; Gangwar, 2010). Different races of silkworms are characterized by undergoing one, two or several uninterrupted generations during the summer.…”
Section: Introductionmentioning
confidence: 99%